Pharmacokinetic profile of carbamazepine and its metabolites on Javanese and Chinese ethnics in Indonesia - Djojosaputro, Mulyadi; ., Sugiyanto; Hubeis, A. Aziz; Ismadi, M. (INDONESIAN JOURNAL OF PHARMACY, 2010)
Carbamazepine  (CBZ)  is  an  anticonvulsant  widely  used  for  epilepsy treatment. However, it is difficult  to  establish suitable dosage  regimens  for  this drug because of the variation on its pharmacokinetics profiles. A lot of evidences indicate  that  ethnic  differences  may  affect  pharmacokinetics  and  hence  dosage requirements. The study was conducted to document pharmacokinetic profile of CBZ  and  its  metabolites  on  Javanese  and  Chinese  ethnics  in  Indonesia.  The study was carried out in 26 Javanese and 24 Chinese ethnics healthy volunteers, Blood  samples  were  collected  serially.  Carbamazepine  and  its  metabolites was  assayed  by  HPLC.  The  results  showed  that  no  significant  differences in  pharmacokinetic  parameters  were  observed  between  both  ethnics.  The values  of  AUC0-~, Cmax,  Tmax,  and  t1/2 CBZ  on  Javanese  ethnic  are  652.44  ± 254.79  µg/mL.h,  8.93  ±  3.58  µg/mL,  11.53  ±  2.16  h,  and  43.70  ±  12.50  h respectively,  while  on  Chinese  ethnic  are  830.27  ±  809.57  µg/mL.h,  13.29  ± 17.46  µg/mL,  9.97  ±  2,90  h,  and  41.27  ±  13.50  h,  respectively.  However,  a significant  interindividual  variation  in  CBZ  metabolism  was  observed  in  both ethnics  as  shown  in its  large  variation in metabolic  ratio.  The  metabolic  10,11-epoxide  CBZ  and  trans-10,11  CBZ  concentration  ratio  on  Javanese  ethnic are 0.07 ± 0.03 and 0.13 ± 0.14, while on Chinese ethnic are 0.35 ± 0.99 and 0.14  ±   0.11.   It  can  be  concluded,  that  the  Pharmacokinetic  of  CBZ  and  its metabolites  on  Javenes  ethnic  is  not  different  compared  to  Chinese  ethnic.  In addition, there  is  a  significant  interindividual  variation  in  pharmacokinetics profile on both ethnics.Key words: Carbamazepine, Javanese, Chinese, pharmacokinetics, epilepsy